The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.22514/sv82.102013.2
|View full text |Cite
|
Sign up to set email alerts
|

Administration of protein C concentrates in patients without congenital deficit: a systematic review of the literature

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our study confirmed previous findings [11,12,14,16,29] that the use of protein C zymogen is not associated with an increased risk for thrombosis or bleeding. As a matter of fact, incidence of bleeding complications in our study was lower than reported in other case series [30].…”
Section: Key Findingssupporting
confidence: 92%
See 3 more Smart Citations
“…Our study confirmed previous findings [11,12,14,16,29] that the use of protein C zymogen is not associated with an increased risk for thrombosis or bleeding. As a matter of fact, incidence of bleeding complications in our study was lower than reported in other case series [30].…”
Section: Key Findingssupporting
confidence: 92%
“…Overall, over 340 patients with non-congenital protein C deficits received protein C zymogen and had the results published [16]. No bleeding complications related to the study drug were reported, and most studies underlined normalization of inflammatory markers and of coagulation abnormalities.…”
Section: Previous Relevant Studiesmentioning
confidence: 99%
See 2 more Smart Citations